Y a-t-il un guide dans la rédaction ? - Daniel Elmiger (Glad!)
In guidelines for non-sexist / inclusive language, instructions are given for a more equitable use of nouns (and satellite forms) referring to humans. Such guides exist for many languages, including for French since the 1980s. In France, two guides seem to have had a decisive influence on the public debates that have emerged since 2017: one has promoted forms that were not previously advocated, and the other has strongly contributed to anchoring the adjective inclusif/inclusive in both specialised and non-specialised discourse. However, many other designations exist for the guides and the subject matter they address.